The secret garden - Burnett, Frances Hodgson; Mohammed, Waheed ([Cairo] bayt alkotob publishing, 2025)
Ten-year-old Mary comes to live in a lonely house on the Yorkshire moors and discovers an invalid cousin and the mysteries of a locked garden
English stories
Keywords: English fiction